2007
DOI: 10.1007/s00256-007-0291-9
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies of the long head of the biceps brachii tendon: clinical significance, MR arthrographic findings, and arthroscopic correlation in two patients

Abstract: Two patients with clinically relevant anomalies of the long head of the biceps brachii tendon (LHBT) are presented with MR arthrography and surgical correlation. Such variations in the LHBT can mimic tears of the tendon itself or the adjacent superior labrum both on MR arthrography and at surgery. MR arthrographic features are recognizable and allow for correct prospective diagnosis, possibly averting unnecessary surgery. Although further study is needed, patients with these anomalies may be at increased risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“…The intertubercular sulcus has been described in cases where the LHBT is hypoplastic [Gaskin et al, 2007], although it is not present when the LHBT is absent [Ghalayini et al, 2007]. The intertubercular sulcus appeared in Carnegie stage 18 embryos in relation to the LHBT primordium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intertubercular sulcus has been described in cases where the LHBT is hypoplastic [Gaskin et al, 2007], although it is not present when the LHBT is absent [Ghalayini et al, 2007]. The intertubercular sulcus appeared in Carnegie stage 18 embryos in relation to the LHBT primordium.…”
Section: Discussionmentioning
confidence: 99%
“…The fetal specimens that we analyzed showed that the LHBT was free in the articular cavity or joined to the articular capsule by a mesotendon. The origin of the tendon in the articular capsule and the supraspinatus zone has been described [Egea et al, 2010;Gaskin et al, 2007;Hyman and Warren, 2001;MacDonald, 1998;Richards and Schwartz, 2003;Wahl and MacGillivray, 2007;Yeh et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…Without the long head of the biceps tendon there was no humeral head depressor effect to help control superior humeral head translation (Keefe and Lowe, 2005). A recent report by Gaskin et al (2007) described two cases of anomalous biceps tendons associated with anterior labral tears and instability. In both cases the long head of the biceps was present but hypoplastic.…”
Section: Discussionmentioning
confidence: 97%
“…These anomalies may increase the risk of acquiring shoulder instability. 2 Thus recognition of abnormalities of the biceps tendon is important because they are a common source of shoulder pain both alone or in combination with abnormalities of the rotator cuff, labrum, and other structures. Knowledge of this anomaly can be helpful in explaining unusual signs on magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…1 The knowledge of these variants may be relevant for both glenohumeral surgery and arthroscopy. 2 The intra-articular bifurcate anomaly of the LHBT origin is relatively less frequent. This anomaly is usually undetectable on preoperative evaluations such as magnetic resonance imaging and ultrasound because of an interpretational difficulty and lack of preoperative insight toward the anomalous biceps long head.…”
mentioning
confidence: 99%